(3JQSd VjGA GdOjf GHf GdCKjQs - (3fUQ Gddg Hf eMeO Hf eMeO Hf YHO GdcQje GdTjHGfqj, GdLRQj, CHh GdaJM, VjGA GdOjf, GdeYQha HGHf GdCKjQ GdcGJH,J (B637 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI (B: (3QH Jee HaVdc cJGH cJHg Edi GdOjhGf GdYRjR GdfHhi YfO hUhd LdGd GdOjf efc HQfi Hf eMeO NhGQRe TGg EdiCQV GdYQGb Ydi bUO GdYHK hGdaSGO ai GdHdGO hGdPgH hGdSac s
(3BNQgG (B:s
(3hdZh GddGZi aYdjc HgPg GdecQeI GdJi CeQ Gddg QShdg HbUOgG hde jNGda GdYbd Mce GdTQjYI ai eRjI MeOgG hGdSdGe Zf TGA Gddg JYGdi fLRJ QSGFd GHf GdCKjQ s
(3jdjgG GdefThQ GdPi cJHg UGMH GdbUQ Edi CSO GdOjf TjQchg ai CQHY UaMGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B31 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B98s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B176 s
Keywords: (3GdCOHs